Irish Born Trilogy: Born in Shame - Book 3 - Roberts, Nora (New York : Brilliance Audio, 2007)
Her life turned upside-down after learning the identity of her real father, successful graphic artist Shannon Bodine reluctantly sets out to meet her family in County Clare and discovers the meaning of true love.